2008
DOI: 10.3758/pp.70.2.199
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in spatial perception of body tilt

Abstract: The tendency for observers to overestimate slant is not simply a visual illusion but can also occur with another sense, such as proprioception, as in the case of overestimation of self-body tilt. In the present study, distortion in the perception of body tilt was examined as a function of gender and multisensory spatial information. We used a full-body-tilt apparatus to test when participants experienced being tilted by 45º, with visual and auditory cues present or absent. Body tilt was overestimated in all co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Participants were tilted on their left-hand side and had to discriminate the tilt of a bar in three conditions, visual, haptic and bimodal. Although previous research has shown effects given by gender in the perception of body orientation (41), we tested this aspect in our study and observed no influence of gender (see Supplementary Materials). Our results show biases that reflect undercompensation or overcompensation of body tilt depending on the encoding sensory modality and subjects' age.…”
Section: Discussionmentioning
confidence: 85%
“…Participants were tilted on their left-hand side and had to discriminate the tilt of a bar in three conditions, visual, haptic and bimodal. Although previous research has shown effects given by gender in the perception of body orientation (41), we tested this aspect in our study and observed no influence of gender (see Supplementary Materials). Our results show biases that reflect undercompensation or overcompensation of body tilt depending on the encoding sensory modality and subjects' age.…”
Section: Discussionmentioning
confidence: 85%
“…To solve the slope task, participants had to focus on all the cues (visual, vestibular, and kinesthetic) deriving from the inclination of the enclosure relative to the horizontal plane (determined by the gravity axis). Other tasks that share a similar emphasis on the vertical/horizontal reference frame have also shown a sex difference in favor of men-for example, the estimation of body tilt ( Naylor & McBeath, 2008), the verbal judgment of hill slants ( Proffitt et al, 1995), the Water Level test, and the Rod and Frame test ( Linn & Petersen, 1985;Voyer et al, 1995). It has been suggested that a sex difference might arise because women experience a difficulty in the processing of vestibular information ( Sholl, 1989).…”
Section: Sex Difference In the Use Of A Multi--modal Directional Cuementioning
confidence: 99%
“…One striking anecdote of this phenomenon is to consider the streets in San Francisco. Even in pictures, these streets appear to be astronomically steep, but the steepest street in San Francisco is reportedly 17.5 degrees (Naylor and McBeath, 2008 ). The general overestimation of geographical slant was originally reported in the literature by Kammann ( 1967 ), but more recently it has been systematically studied by Proffitt and colleagues (Proffitt et al, 1995 ).…”
Section: The Economy Of Social Resources and Its Influence On Spatialmentioning
confidence: 99%